Pengaruh Daya Tarik Iklan, Celebrity Endorser, Brand Image Dan Persepsi Harga Terhadap Keputusan Pembelian Pengguna Shopeefood (Studi Kasus Pada Konsumen Mahasiswa Universitas Islam Malang) - Moh. Nur Dafa Sidqi; Rois Arifin; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Based on research conducted with the aim of analyzing the effect of advertising attractiveness, celebrity endorser, brand image and price perception on purchasing decisions on shopee food users. The sample in this study were 92 shopee food users. The sampling technique used is purposive sampling where every customer who has made a repeat purchase has the opportunity to be a sample. The analytical method used in this study is multiple linear regression analysis with hypothesis testing using the F test and t test. From this study it is known that partially and simultaneously the variables of advertising attractiveness, celebrity endorser, brand image and price perception on purchasing decisions Keywords: Advertising Appeal, Celebrity Endorser, Brand Image, Price Perception, Purchase Decision